The future of medical students; perspectives and expectations: a cross-sectional study in Mashhad University of Medical Sciences - Majid Khadem-Rezaiyan; Zahra Zeinalipour; Zahra Rashidtorabi; Masoud Youssefi (Tabriz University of Medical Sciences, 2018)
Background: Health decision makers should be able to predict attitudes of medical students and factors influencing their tendency to allocate enough resources and university vacancy. These attitudes may not be always congruent with the actual and prominent health needs of society. The purpose of this study was to delineate medical students' career prospects and general expectations. Methods: This cross-sectional study was conducted on 200 medical students who were selected through a multi-stage sampling method from all educational stages (basic science, physiopathology, clinical clerkship, internship) studying at Mashhad University of Medical Sciences in 2016-2017. The first five priorities for work after graduation and first five priorities for residency were studied and the Priority-Percentage Index (PPI), which considers the percentage and a reverse scoring for the priority of selecting an item, was calculated. Results: Principally, "pursuing one of the medical specialities" was the most desired career choice (3.73 PPI) followed by "employment in private practice" (2.08 PPI) regardless of gender, native status, and stage of education. Although the most preferred specialities were ophthalmology (1.99 PPI), cardiology (1.66 PPI) and radiology (1.44 PPI), the trend of interest varied by educational stage. Conclusion: Income and reputation have a significant influence on medical students' attitude toward specialities. Therefore, it is crucial that policy-makers note preferences in specialities and consider the society's demand in the field of healthcare.